Methods of applying nuclear simulation technology to the dynamic site testing of digital I&C system—Ⅱ: DCS-testing methods. (June 2017) - Lin, Meng; Li, Yankai; Yang, Zongwei; Hou, Yousheng; Yang, Yanhua
Highlights: OLVT of DCS is classified into four major types according to the mode of implementation. Application conditions of different testing methods are summarized. OLVT can apply to any DCS system by flexible choice of the testing methods. Abstract: Although engineering simulators were used for the V&V of NPP DCS, there has been no systematic evaluation of its use for site testing. This study summarizes on-line virtual testing (OLVT) methods for DCS site testing to guide the on-site V&V activities. DCS-testing methods for different types of systems are described in detail. We classified OLVT into four types according to the mode of implementation way: 1) hard wiring closed-loop test, 2) network connection closed-loop test, 3) signal injection open-loop test, and 4) integrated automatic comparison open-loop test. Each of the testing methods is illustrated in detail with a typical application. These four kinds of testing methods differ in their characteristics, but flexible application of them should be performed based on the specific conditions and requirements of site testing. Following the guide lines present here, OLVT can be applied to generalized DCS systems in site testing.